The Immortal Victims: Representations of Women in Vampire Fiction - Kiertokari, Aliisa (fi=Turun yliopisto|en=University of Turku|, 2017)
This thesis examines the representations of women and the evolution of female characters in vampire fiction. My primary sources are Bram Stoker’s Dracula, Anne Rice’s Interview with the Vampire and Stephenie Meyer’s Twilight, although I occasionally consult other titles from the genre. I chose the topic due to the increasing popularity of the vampire as a literary character, especially during the recent decades. The topic is therefore current and it is useful to study the images of women and gender relationships that the vampire novels portray. The main focus of my study is to analyze the female characters, but in order to provide adequate background information, I will also briefly introduce the history of the genre and the vampire character before the actual analysis. This will allow me to coherently examine the differences between the sexes in my materials as well as to provide consistent conclusions about the possible developments within the genre. My theoretical background is feminist literary theory, but I also utilize genre studies when it is appropriate. The main feminist theorists whose arguments about female representations I have discussed in the thesis are Nancy Armstrong, Toril Moi and Judith Butler. My hypothesis is that the women in vampire fiction have not developed as significantly as the genre in itself. The genre and the vampire character have undergone noticeable changes since the first literary vampires, but women still occupy a weak status within the genre. By analyzing the works by Stoker, Rice and Meyer I will show how women are systematically portrayed as lesser characters in vampire literature. On the other hand, I will discuss the few exceptions to the rule, such as Sheridan Le Fanu’s novella Carmilla, and the possible significations of these exceptions in relation to the future of vampire fiction.